1993
DOI: 10.1002/j.1460-2075.1993.tb05790.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathway correcting DNA replication errors in Saccharomyces cerevisiae.

Abstract: Mutation of predicted 3′‐‐>5′ exonuclease active site residues of Saccharomyces cerevisiae POL3 DNA polymerase (delta) or deletion of the PMS1 mismatch repair gene lead to relative (to wild type) spontaneous mutation rates of approximately 130 and 41, respectively, measured at a URA3 reporter gene inserted near to a defined replication origin. The POL3 exonuclease‐deficient mutant pol3‐01 generated most classes of single base mutation in URA3, indicating a broad specificity that generally corresponds to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
282
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(309 citation statements)
references
References 34 publications
26
282
0
Order By: Relevance
“…The inviability of pol3-R696W could be caused by (i) severely impaired catalytic activity of Polδ or (ii) the accumulation of lethal mutations in other essential genes because of a dramatic decrease in the fidelity of Polδ. Such a "mutation catastrophe" has been previously described for yeast that are defective simultaneously in two replication error-avoidance mechanisms (exonucleolytic DNA polymerase proofreading and MMR) (17) and for E. coli carrying a defective exonuclease subunit of Pol III (18). If pol3-R696W encodes a nonfunctional polymerase, haploid cells expressing the mutant allele would not be able to replicate their DNA and divide, as observed previously (19) and in this study (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The inviability of pol3-R696W could be caused by (i) severely impaired catalytic activity of Polδ or (ii) the accumulation of lethal mutations in other essential genes because of a dramatic decrease in the fidelity of Polδ. Such a "mutation catastrophe" has been previously described for yeast that are defective simultaneously in two replication error-avoidance mechanisms (exonucleolytic DNA polymerase proofreading and MMR) (17) and for E. coli carrying a defective exonuclease subunit of Pol III (18). If pol3-R696W encodes a nonfunctional polymerase, haploid cells expressing the mutant allele would not be able to replicate their DNA and divide, as observed previously (19) and in this study (Fig.…”
Section: Resultssupporting
confidence: 81%
“…In the mutation-catastrophe scenario, lethal mutations would accumulate during replication, and pol3-R696W cells would be expected to proceed through a number of cell cycles before cell division ceases. This was previously observed for the proofreadingand MMR-deficient yeast cells (17). Microscopic examination after tetrad dissection showed that the pol3-R696W cells were able to divide and form microcolonies of varying size (estimated at ∼100 cells on average) before cell division stopped (Fig.…”
Section: Resultssupporting
confidence: 78%
“…In yeast 22,23 and mice 7,16 , expression of pol-d mutants analogous to those studied here brought about an increase in spontaneous mutation rates and, in the mouse, predisposition to cancer. These results suggested that the MMR system was unable to deal with the increased load of mutations, similarly to what was observed in E. coli 20 .…”
Section: Resultsmentioning
confidence: 65%
“…Indeed, in the yeast mutants in which pol delta or epsilon proofreading is selectively inactivated, the mutations rates are 10-100 times higher than the wild-type strains. [26][27][28] Recently, mice carrying artificial alleles with substitutions at essential amino-acid residues in the proofreading domains of pol delta 29,30 and epsilon 31 have been reported. The observed mutation rates were indeed significantly elevated over the wild-type levels.…”
Section: Introductionmentioning
confidence: 99%